Shorter Digestion Times of Donor Islets Is Associated With Better Islet Graft Function After Islet Transplantation - Chia-Hao Wang; Christopher Orr; Jeannette Hacker-Stratton; Mohamed El-Shahawy; Keiko Omori; Meirigeng Qi; Fouad Kandeel (Cell Transplantation)
Although islet transplantation is effective in reducing severe hypoglycemia events and controlling blood glucose in patients with type 1 diabetes, maintaining islet graft function long-term is a significant challenge. Islets from multiple donors are often needed to achieve insulin independence, and even then, islet function can decline over time when metabolic demand exceeds islet mass/insulin secretory capacity. We previously developed a method that calculated the islet graft function index (GFI) and a patient’s predicted insulin requirement (PIR) using mathematical nonlinear regression. Both PIR and GFI could be used by physicians as tools to monitor islet graft function and to guide supplementing the patient with exogenous insulin to prevent beta-cell exhaustion. This study investigates the factors relating to the islet preparation process, as well as donor and recipient characteristics, and assessed their associations with PIR and GFI after transplantation. The goal is to determine the most relevant factors that influence islet graft function after transplantation. We examined the effects of donor and recipient characteristics, and islet processing factors on posttransplanted PIR and GFI. The PIR and GFI at 3 months were calculated using patients’ baseline insulin intake, posttransplant 2-h postprandial blood glucose, and glucagon-stimulated C-peptide. Thirteen transplants that resulted in progressive decline in patients’ weekly averaged insulin intake over the initial weeks after transplant (assuming constant glucose level) with available 3-month PIR and GFI data were chosen for the investigation. Univariate analyses were performed to assess the effects of donor and recipient characteristics and islet processing factors on islet graft function as reflected by PIR and GFI. The PIR and GFI were treated as continuous response variables in separate linear regression models. Shorter digestion time of isolated donor islets were associated with lower PIR ( P = 0.014) and a higher GFI ( P = 0.027) after transplantation. Islet injury related to digestion enzyme exposure influenced islet function as estimated using PIR and GFI post-transplantation.